1980
DOI: 10.2527/jas1980.5061122x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sampling Intervals and Digesta Markers on Abomasal Flow Determinations

Abstract: Four sampling schedules and three digesta markers were investigated with abomasally-cannulated steers. Nonammonia nitrogen flow through the abomasum was used as the criterion for comparison. A single diet, consisting of ground corn cobs and cane molasses and supplemented with soybean meal to 11.5% crude protein, was used. Each steer was fed hourly to maintain a constant digesta flow. Digesta markers used were: polyethylene glycol (PEG) and chromic oxide (Cr2O3), as external markers for the liquid fraction and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
3

Year Published

1987
1987
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 10 publications
1
15
0
3
Order By: Relevance
“…Knight et al (1972) found that the amount of tungstic acid-precipitable CP entering the abomasum varied over time in contrast to similar entry rates of DM. Similarly, flow of nonammonia nitrogen was not affected by sampling of abomasal digesta at either 24-, 48-, or 72-h intervals (Waller et al 1980) nor was forestomach digestion of OM and starch affected by 2-or 6-d intermittent collection ofabomasal digesta and feces (Theurer et al 1981). Forestomach digestion of CP in the present study was low and as in the study by Theurer et al (198 l …”
supporting
confidence: 54%
“…Knight et al (1972) found that the amount of tungstic acid-precipitable CP entering the abomasum varied over time in contrast to similar entry rates of DM. Similarly, flow of nonammonia nitrogen was not affected by sampling of abomasal digesta at either 24-, 48-, or 72-h intervals (Waller et al 1980) nor was forestomach digestion of OM and starch affected by 2-or 6-d intermittent collection ofabomasal digesta and feces (Theurer et al 1981). Forestomach digestion of CP in the present study was low and as in the study by Theurer et al (198 l …”
supporting
confidence: 54%
“…Para determinar el factor de indigestibilidad mediante la producción de heces, se utilizó como marcador interno la fibra detergente ácido indigerible (FDAi) 69 , asumiendo un porcentaje de recuperación del 80 % 63 . Para determinar esta fracción, se realizó la incubación ruminal in vitro durante 144 horas 10,15 , de un gramo de las muestras de forraje, suplemento y heces colectadas en cada periodo, las cuales se incubaron por duplicado en bolsas ANKOM F-57 con tamaño de poro 25 µm, en un incubador DAISYII siguiendo el protocolo descrito por el fabricante del equipo para la determinación de la DIVMS.…”
Section: Variables De Respuestaunclassified
“…To obtain estimates of fecal excretion, indigestible neutral detergent fiber (iNDF) was used as an internal indicator, as proposed by Waller et al (1980). iNDF was determined by ruminal incubation of samples of food, leftovers and feces WCSEd FOR LACTATING COWS for 240 h, into F57 filters (ANKON ® Technology Corporation), and an analysis of neutral detergent fiber was then performed (Lippke et al 1986).…”
Section: Methodsmentioning
confidence: 99%